DICATATORSHIP AND EDUCATION:CONNECTIONS TO BE RECONSIDERED - Solon Eduardo Annes Viola; Paulo Peixoto de Albuquerque (Editora da Universidade de Santa Cruz do Sul, 2015)
The last four decades of XX century were decisive to brazilian educational process. In this period, national democracy spaces were interrupted, and a militar dictatorship structures, under the american national doctrine, a transformation of brazilian society trough fear imposition and the Market freedom speech. In several educational systems, the despotic state supressed the national university creation devoted to research, while determined curricula orientated to citizenship denial and by empty justifications to repression and authoritary speech. The process that has leaded to redemocratization was composed by the interruption of economic growth, the civil society reorganization, and social movements participation. In the education field, new alternatives were born, from popular education recovery to new activities on research. This text recovers the human rights purposes like one of the conceivables alternatives to the constitution of an educational process dedicated to students and teachers emancipation in dialogue with society.